Strategi Self-Regulated Learning untuk Mengoptimalkan Kreatifitas dan Keberbakatan Peserta Didik - Nafisha Arifa Azahra; Chici Cahyaningrum; Nur Qomariyah; Wahyu Musrifah; Ivo Sindia Nur Azizah (Al-Kindi, 2026)
This study aims to identify and examine effective Self-Regulated Learning (SRL) strategies to optimize students' creativity and giftedness potential. The method employed is a qualitative approach utilizing library research. All data were gathered from secondary sources, including scientific journal articles, textbooks, and previous research reports, which were then analyzed using thematic content analysis. The results indicate that SRL, which integrates metacognition, motivation, and active behavior, plays a crucial role in transforming the raw intellectual potential of gifted children into concrete academic achievements. The implementation of SRL strategies through student-centered learning models such as Contextual Teaching and Learning (CTL), Brain Based Learning (BBL), and blended learning has proven effective in stimulating creative thinking skills (encompassing fluency, flexibility, elaboration, and novelty) and providing learning flexibility tailored to the unique characteristics of gifted students. Practical recommendations from this study emphasize the importance of an educational ecosystem that fosters thinking autonomy and the sustainable development of robust independent character.